Principles of Health Interoperability HL7 and SNOMED - Benson, Tim.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Interoperability between healthcare computer systems depends on us developing, implementing and deploying appropriate standards, such as HL7 and SNOMED CT, working together as a tightly specified language. The documentation of HL7 and SNOMED runs to tens of thousands of pages and creates a steep learning curve and barrier to entry. Principles of Health Interoperability HL7 and SNOMED provides a clear introduction to these standards, explaining the core principles for the health IT professional, student, clinician and healthcare manager.
Keywords: Medicine; Public health; Medical records -- Data processing; Medicine & Public Health; Health Informatics; Public Health; Medicine/Public Health, general